[Skull base tumors] - Ahlhelm, F; Nabhan, A; Naumann, N; Grunwald, I; Shariat, K; Reith, W (2005)
Modern imaging techniques have great importance in the diagnosis and therapy of skull-base pathologies. Many of these lesions, especially in relation to their specific location, can be evaluated using CT and MR imaging. Tumors commonly found in the anterior skull base include carcinoma, rhabdomyosarcoma, esthesioneuroblastoma and meningioma. In the central cranial fossa, nasopharyngeal carcinoma, metastases, meningioma, pituitary adenoma and neurinoma have to be considered. The most common neoplasms of the posterior skull base, including the CP angle, are neurinoma, meningioma, nasopharyngeal carcinoma, chordoma and paraganglioma. One major task of imaging is the evaluation of the exact tumor extent as well as its relationship to the neighboring neurovascular structures. The purpose of this review is to recapitulate the most important anatomical landmarks of the skull base. The typical imaging findings of the most common tumors involving the skull base are also presented.